(untitled) (Namibian Journal of Linguistics, Literature and Communication Studies, 2023)
This paper attempts to highlight the story of a whole community of the Gikuyu people who inhabited the ridges of Kameno and Makuyu in Ngugi wa Thiongo’s The River Between. The paper will integrate the public aspects of the novel with the dramatic actions of the private individuals. The main characters, as protagonists in the conflict, represented opposing forces within the society and yet they remained convincing as human beings. Alienation and Identity Crisis on protagonists and other significant fictional characters will take the centre stage of this paper. There are so many editions of The River Between but this paper used the 1988 version, ISBN 043590017X.